Association Between H. pylori Infection and Colorectal Polyps: A Meta-Analysis of Observational Studies - Lu, Depeng; Wang, Mingyu; Ke, Xiquan; Wang, Qiangwu; Wang, Jianchao; Li, Dapeng; Wang, Meng; Wang, Qizhi (Frontiers in Medicine, 2022)
Background It has been suggested that Helicobacter pylori (H. pylori) infection is associated with hypergastrinemia and proliferation of colorectal mucosa via direct stimulation, dysbiosis of the gut microbiome, and changes in the gut microbiome, all of which may lead to the formation of colorectal polyps. However, the consensus remains lacking regarding whether H. pylori infection is independently associated with colorectal polyps and whether the association differs according to histological type of colorectal polyps. To summarize the current evidence regarding the relationship between H. pylori infection and colorectal polyps, we conducted a meta-analysis of related observational studies according to the histological types of colorectal polyps. Methods Observational studies investigating the association between H. pylori infection and colorectal polyps using multivariate analyses were included by search of PubMed, Embase, and Web of Science. A random-effects model was adopted to combine the results. Results Seventeen studies that include 322,395 participants were analyzed. It was shown that H. pylori infection was independently associated with overall colorectal polyps (odds ratio [OR]: 1.67, 95% CI: 1.24–2.24, p < 0.001; I2 = 73%). According to the histological type of colorectal polyps, H. pylori infection was independently associated with adenomatous polyps (APs; OR: 1.71, 95% CI: 1.47–1.99, p < 0.001; I2 = 86%), advanced APs (OR: 2.06, 95% CI: 1.56–2.73, p < 0.001; I2 = 0%), and hyperplastic polyps (HPs; OR: 1.54, 95% CI: 1.02–2.30, p = 0.04; I2 = 78%). Evidence based on only one study showed that H. pylori infection was not associated with sessile serrated polyps (SSPs; OR: 1.00, 95% CI: 0.93–1.07, p = 0.99). Conclusions Current evidence from case-control and cross-sectional studies suggested that H. pylori infection was independently associated with colorectal APs, advanced APs, and HPs, but not with SSPs. These findings suggested H. pylori infection may be a possible risk factor of colorectal polyp, which is important for the prevention of colorectal polyp in the adult population.